A prospective population-based study of menopausal symptoms - Dennerstein, L; Dudley, E C; Hopper, J L; Guthrie, J R; Burger, H G (Obstetrics and gynecology (New York. 1953), 2000)
To identify symptoms that change in prevalence and severity during midlife and evaluate their relationships to menopausal status, hormonal levels, and other factors. In a longitudinal, population-based study of 438 Australian-born women observed for 7 years with an 89% retention rate, 172 advanced from premenopause to perimenopause or postmenopause. Annual measures included a 33-item symptom check list; psychosocial, lifestyle, and health-related factors; menstrual status; hormone usage; and blood levels of follicle-stimulating hormone and estradiol (E2). Increasing from early to late perimenopause were the number of women who reported five or more symptoms (+14%), hot flushes (+27%), night sweats (+17%) and vaginal dryness (+17%) (all P <.05). Breast soreness-tenderness decreased with the menopausal transition (-21%). Trouble sleeping increased by +6%. The major change in prevalence was from early to late perimenopause, except for insomnia, which showed a gradual increase. Those variables most related to onset of hot flushes were number of symptoms at early perimenopause (P <.05), having an unskilled or no occupation (P <.05), more than 10 pack-years of smoking (P <.01), and decreased E2 (P <.01). The onset of night sweats increased with the change in E2 (P <.05). The onset of vaginal dryness decreased with more years of education (P <.05). Trouble sleeping was predicted by prior lower well-being (P <.01), belief at baseline that women with many interests hardly notice menopause (P <.01), and hot flushes (P <.01). Although middle-aged women are highly symptomatic, the symptoms that appear to be specifically related to hormonal changes of menopausal transition are vasomotor symptoms, vaginal dryness, and breast tenderness. Insomnia reflected bothersome hot flushes and psychosocial factors.